Quantitative pulmonary pharmacokinetics of tetrandrine for SARS-CoV-2 repurposing: a physiologically based pharmacokinetic modeling approach - Furun Wang; Furun Wang; Liuhan Dong; Juanwen Hu; Shijie Yang; Lingchao Wang; Zhiwei Zhang; Wenpeng Zhang; Xiaomei Zhuang (Frontiers Media S.A., 2024)
Tetrandrine (TET) has been traditionally used in China as a medication to treat silicosis and has recently demonstrated anti-SARS-CoV-2 potential in vitro. By recognizing the disparity between in vitro findings and in vivo performance, we aimed to estimate the free lung concentration of TET using a physiologically based pharmacokinetic (PBPK) model to link in vitro activity with in vivo efficacy. Comparative pharmacokinetic studies of TET were performed in rats and dogs to elucidate the pharmacokinetic mechanisms as well as discern interspecies variations. These insights facilitated the creation of an animal-specific PBPK model, which was subsequently translated to a human model following thorough validation. Following validation of the pharmacokinetic profile from a literature report on single oral dosing of TET in humans, the plasma and lung concentrations were predicted after TET administration at approved dosage levels. Finally, the antiviral efficacy of TET in humans was assessed from the free drug concentration in the lungs. Both in vivo and in vitro experiments thus confirmed that the systemic clearance of TET was primarily through hepatic metabolism. Additionally, the lysosomal capture of basic TET was identified as a pivotal factor in its vast distribution volume and heterogeneous tissue distribution, which could modulate the absorption dynamics of TET in the gastrointestinal tract. Notably, the PBPK-model-based unbound lung concentration of TET (1.67-1.74 μg/mL) at the recommended clinical dosage surpassed the in vitro threshold for anti-SARS-CoV-2 activity (EC90 = 1.52 μg/mL). Thus, a PBPK model was successfully developed to bridge the in vitro activity and in vivo target exposure of TET to facilitate its repurposing.